Glass Production from River Silica of Bangladesh: Converting Waste to Economically Potential Natural Resource: 10.32526/ennrj/20/202100124 - Rajib, Mohammad; Hossain, Md. Fahad; Parveen, Mahfuza (Environment and Natural Resources Journal, 2022)
The Ganges-Brahmaputra river system at the Bengal Basin carries large amounts of sediments on the way to finally deposit at the Bay of Bengal. Those river-transported sediments form bar deposits during dry season in many areas of Bangladesh and accumulate economic mineral depositions at suitable geological environments. Dredging is a must for most of those rivers for proper navigation, as well as protecting bank erosion, which generates millions of tons of waste sand. The dredged materials from river beds are mostly composed of silicate minerals, especially quartz and feldspar along with several dark colored heavy minerals. Like the industrial processing of heavy minerals from bulk sands, various physical separation techniques can be utilized for the beneficiation of silica from those river-born silicate minerals in dredged sands. Those silica have been successfully upgraded to near-glass sand grade in the laboratory, however, they have yet to be utilized for any kind of commercial venture. The present study attempts characterization of several river sands through physical separation and laboratory analysis. The upgraded silica was successfully compared with several quality glass sands and laboratory production of glasses. This experimental production of glass from upgraded silica could potentially be economical considering its industrial application with positive environmental consequences through minimizing the dredging cost, increasing the navigability of the river and ecological balance along the flood plain.